1980
DOI: 10.1049/ip-c.1980.0014
|View full text |Cite
|
Sign up to set email alerts
|

Fast power-flow solution by the method of reduction and restoration

Abstract: The paper gives a fast power-flow-solution technique retaining only voltage-controlled busbars in the iterative process. Voltages are represented in rectangular co-ordinates, and the change in voltages from the assumed values is estimated in the iterative process. Power mismatches are computed only at two stages instead of at every iteration. After obtaining convergence, the original network is restored and the voltages of the load busbars are calculated. The essential features of the method are (a) only volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A fast load flow method proposed in [2,14] is adopted in this study. In this method, the load busbars are eliminated, retaining only generator busbars for the iterative process.…”
Section: Methods Of Power System Reduction and Restorationmentioning
confidence: 99%
“…A fast load flow method proposed in [2,14] is adopted in this study. In this method, the load busbars are eliminated, retaining only generator busbars for the iterative process.…”
Section: Methods Of Power System Reduction and Restorationmentioning
confidence: 99%
“…The classical model is used to study the transient stability of a power system for a period of time during which the dynamic behavior of the system is dependent largely on the stored energy in the rotating inertias. It's the simplest model and requires a minimum amount of data [6][7][8][9][10] .…”
Section: The Transient Stability Programmentioning
confidence: 99%
“…The second-order Newton-Raphson method, where the second-order derivatives were included in the computation process, was applied [5], and it was reported that this method gave tens of times faster results [6]. Another approach initially decreases the system size by focusing only on the voltage buses, and then applying the Newton-Raphson method [7]. The branch outage simulation results of this method were compared to the second-order Newton-Raphson method, and it was found that the former gave better results [5].…”
Section: Introductionmentioning
confidence: 99%